French in 3 months : your essential guide to understanding and speaking French - Overy, Ronald; Lecanuet, Jacqueline (London : Dorling Kindersley Limited, 2022)
Learn to speak French in just three months with this practical and comprehensive self-study language course.Whether you're a complete beginner or wanting to refresh your knowledge, Hugo: French in Three Months will have you speaking French fluently in just 12 weeks. With a fresh new look and an accompanying audio app, the latest edition of this classic self-study course provides all the resources needed to speak, read, and write in French.The 12 weekly chapters contain lessons on the key grammatical structures and present a range of useful vocabulary, along with exercises to reinforce your learning. The essentials of French grammar are clearly explained and tested in conversational exercises, giving you the authentic feel of the language. In addition to a written "imitated pronunciation" guide, which replaces French sounds with English syllables you're already familiar with, the new audio app also allows you to perfect your pronunciation - at home or on the go. Whether you're learning French for work, a future holiday, or because you're interested in languages, this course is the perfect place to start. Learning French has never been so easy!
Week 1.--Week 2.--Week 3.--Week 4.--Week 5.--Week 6.--Week 7.--Week 8.--Week 9.--Week 10.--Week 11.--Week 12.--Week 13.--Week 14.--Week 15.--Week 16.
Includes index.
Keywords: FRENCH LANGUAGE; FRENCH LANGUAGE -- SPOKEN FRENCH